Sistem Pengambil Keputusan Rekomendasi Lokasi Wisata Malang Raya Dengan Metode MOORA - Pranata, Aldi Surya; Rosiani, Ulla Delfiana; Mentari, Mustika (P3M Politeknik Negeri Banjarmasin, 2021)
Malang Raya, which consists of Malang City, Malang Regency, and Batu City, is one of the favorite tourist destinations in East Java. The number of tourist attraction locations that offer various advantages of each. This often makes it difficult for local and non-local tourists to choose a tourist destination, in order to be able to maximize their visit time, costs and satisfaction. This study aims to build a decision support system (DSS) for determining tourist locations using the Moora method. This method will provide weighting criteria according to user conditions / preferences, and then perform processing on the data. The built DSS is able to produce recommendations by ranking tourist locations to users according to their preferences. The system built was tested using 5 alternative tourist attraction locations in Batu City and 3 criteria consisting of 1 cost and 2 benefit criteria. Experiments carried out were successful in giving different rankings to 5 alternatives.